2010
DOI: 10.1080/14647891003653401
|View full text |Cite
|
Sign up to set email alerts
|

Depth‐charge in the archive: the documentation of performance revisited in the digital age

Abstract: The debate surrounding the documentation of performance is principally concerned with the ephemerality of the live event, set against the stasis and 'death' that the archive is conventionally believed to represent. The advent of digital technology in live performance has complexified this still further, by altering the architecture, space and dimensionality of the live event. Time-delay, live motion capture, feedback loops, dancing avatars and images projected in and onto the space all conspire to generate a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This changed the definition of an archive from a passive storehouse of information to an active site in which social power is negotiated and constructed (Schwartz, 2008; Schwartz and Cook, 2002). It also created a space for archives to take other forms, which has opened the way for performance art to be viewed as an archive (Allen, 2010; Jones et al, 2009; Stoian, 2002). Changing the understanding of what constitutes an archive changes the notion of memory, moving it from being something represented by a collection to something made and re-made (Schwartz and Cook, 2002).…”
Section: Research Methods and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…This changed the definition of an archive from a passive storehouse of information to an active site in which social power is negotiated and constructed (Schwartz, 2008; Schwartz and Cook, 2002). It also created a space for archives to take other forms, which has opened the way for performance art to be viewed as an archive (Allen, 2010; Jones et al, 2009; Stoian, 2002). Changing the understanding of what constitutes an archive changes the notion of memory, moving it from being something represented by a collection to something made and re-made (Schwartz and Cook, 2002).…”
Section: Research Methods and Challengesmentioning
confidence: 99%
“…Within accounting, circuses have not been a popular theme for historical accounting research although Cummings and St Leon (2009) demonstrated that their study can enhance understanding of historical approaches to financial management. Outside accounting, circuses have been of research interest in historical fields of inquiry that include social history (Arrighi, 2012; Neirick, 2012), performance history (Carmeli, 2003; Fusco, 1994), entertainment history (Stoddart, 2000), management history (Beadle and Könyöt, 2006), economic history (Allen, 2010; Renoff, 2008), political history (Holmgren, 2007), military logistical history (May, 1932) and visual history (Wilson, 2017). Since these disciplines overlap, or are closely aligned with, accounting history, there may be currently unexplored opportunities to consider circuses in the context of other historical accounting research topics.…”
Section: The Written and Performance Archives Comparedmentioning
confidence: 99%
“…Corporate management in the economy, and especially management in agricultural enterprises, requires adequate storage and archiving of documentation [1][2][3][4][5] in enterprises. Archiving documentation in companies is one of the most important tasks that must be done in order to reduce the general risk of doing business in companies [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…One of the important forms of improving corporate governance in Focus is following the problems of documentation movement in companies, but within that monitoring of documentation movement it is necessary to point out that continuous care is taken to reduce real risks for decision makers in companies [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%